Bond strength of the interface between normal concrete substrate and GUSMRC repair material overlay - Abo Sabah, S.H.; Hassan, M.H.; Muhamad Bunnori, Norazura; Megat Johari, M.A. (Elsevier, 2019)
This study investigated the interfacial bond strength between a new Green Universiti Sains Malaysia Reinforced Concrete (GUSMRC)as a repair material and the existing normal concrete substrate (NC)using two methods of surface treatment: grooving and sandblasting. The bond strength was evaluated via the slant shear, splitting tensile, and pull-off strength tests at 7, 28, and 90 days. The results showed that the bond strength of the NC/GUSMRC composite was extremely high, especially with the sandblasting surface treatment. The slant shear results showed that the specimens with sandblasting surface treatment showed almost 1.5 times higher slant shear strength than the strength of those with the grooving surface treatment at the three tested ages. The splitting strengths of the sandblasted samples were 8.3%, 20.7%, and 18.5% higher than the strengths of the grooved samples at 7, 28, and 90 days, respectively. Similarly, the pull-off strengths of the sandblasted specimens were 2.3%, 10%, and 14.5% higher at 7, 28, and 90 days, respectively. The bond strength increased as the age of the composite increased. Therefore, GUSMRC has great potential in the rehabilitation of RC structures. © 2019 Elsevier Ltd